CTLA-4 expression on tregs is needed for suppression of autoimmune uveitis - Minjun Ahn; John Dostal; Priya Hegde; Darren J. Lee (Scientific Reports)
Abstract Uveitis is a leading cause of blindness in the world and autoimmune uveitis is an ocular tissue specific autoimmune disease. Utilizing experimental autoimmune uveitis (EAU), we can interrogate different immune responses in the mouse that are relevant to the human disease. cytotoxic T-lymphocyte antigen 4 (CTLA-4) is an immune checkpoint molecule that has different roles depending on the target tissue. In this work we investigate the role of CTLA-4 on CD4 T cells in ocular tissue during EAU. We find that CTLA-4 is needed for both the severity of disease but also timely resolution of disease. Regulatory T cells (Tregs) that emerge in the spleen during resolution of EAU require CTLA-4 to suppress disease, but ocular Tregs that emerge in the eye do not require CTLA-4 to suppress disease. This report provides an additional understanding of CTLA-4 on Tregs that is specific for ocular tissue. The implications of this work are that circulating Tregs in uveitis patients may require CTLA-4 to suppress ocular inflammation but once in the eye the function of CTLA-4 is dispensable.